125 inspirasi jadi pemimpin jempolan / Engga Aksara, Tezario Vulanda ; penyunting, Chrisna Farmadiani. - ENGGA AKSARA; Tezario Vulanda; Chrisna Farmadiani. (: Javalitera, 2010 / 2012)
184 hlm. ; 19 cm